Penyuluhan Pengurusan Legalitas Lembaga Pengelola Zakat Di Pondok Terpadu Daarul Ilmi Cipeundeuy - Abdul Rojak, Encep; Mujahid; Malki Ahmad Nasir; Fariz Farrih Izadi (Kuras Institute & Scidac Plus, 2023)
The Integrated Islamic Boarding School Daarul Ilmi Cipeundeuy is a major educational institution. This institution was founded in 1993 AD, and has produced many graduates spread across the archipelago. One of the areas taught in theory and practice is zakat management. Every time we enter Ramadan, a zakat committee is formed by pesantren caregivers consisting of teachers and students. Since the establishment of the zakat management institution until 2022 it has not been legalized, even though the rules for zakat management have been regulated in the Zakat Law Number 13/2011. This is also due to limited human resources in terms of positive law. The purpose of this activity is to provide literacy on the legal aspects of zakat management institutions and how to register to become legal zakat managers. The method used in this service is in the form of seminars and mentoring. The seminar was filled with counseling by expert resource persons and service teams, and assistance was also carried out by sharing and mapping the ideal type of zakat manager for this institution. Through this service, pesantren caregivers, asatidz, and administrators of zakat institutions gain literacy about the legal aspects of zakat management and the management of permits. Through assistance carried out with the chairman of Baznas, the type of zakat management institution that is suitable for this institution is the zakat management unit (UPZ).